2018
DOI: 10.1016/j.ijdevneu.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Selective decline in the prevalence of slowly adapting type I mechanoreceptors during development

Abstract: HighlightsElectrophysiological recordings were made from sinus hair follicles in vitro from rats aged from 6 to 50 weeks old.The prevalence of slowly adapting type I mechanoreceptors declined abruptly from 6 to 14 weeks, stabilizing thereafter.In contrast, the prevalence of slowly adapting type II mechanoreceptors did not show any decline over the study period.These findings suggest that there is pruning of Merkel nerve ending mechanoreceptors with age.The importance and triggers for these changes remain to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 1 hyaluronidase experiment, there was no recovery following the second drug application, and data were removed from the analysis. A two-way mixed between and within ANOVA gave no main effects for group or time (F[1, 11] = 0.039, p = 0.847 and F [1,11] = 0.007, p = 0.935, respectively). The interaction gave F(1, 11) = 0.687, p = 0.425.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1 hyaluronidase experiment, there was no recovery following the second drug application, and data were removed from the analysis. A two-way mixed between and within ANOVA gave no main effects for group or time (F[1, 11] = 0.039, p = 0.847 and F [1,11] = 0.007, p = 0.935, respectively). The interaction gave F(1, 11) = 0.687, p = 0.425.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A variety of mechanosensory nerve endings are embedded in the skin and hair follicles [3,4]. Their pharmacological study is important in providing insights into the mechanisms that underlie their function [5][6][7][8][9][10][11]. Numerous in vitro studies [5,7,10,12,13] have shown that the activity of these mechanoreceptors can be recorded for many hours and show identical activity to that observed in vivo [14,15].…”
Section: Introductionmentioning
confidence: 99%